2022
DOI: 10.1108/ijchm-06-2021-0765
|View full text |Cite
|
Sign up to set email alerts
|

Are employee assistance programs helpful? A look at the consequences of abusive supervision on employee affective organizational commitment and general health

Abstract: Purpose Abusive supervision has been a prevalent issue in the workplace. This study aims to explore the consequences of abusive supervision on employee affective organizational commitment and general health in the hospitality industry and further explores the boundary conditions of employee assistance programs (EAPs). Design/methodology/approach The participants of this study were 231 frontline employees from the hospitality industry in Taiwan. Quantitative data was collected using questionnaires from two ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 103 publications
(128 reference statements)
2
25
0
1
Order By: Relevance
“…Offering similar programs to faculty members could decrease stress resulting from their role conflict and lead to less emotional exhaustion, ultimately resulting in lower turnover intention. Third, early intervention and support for such faculty assistance programs ( Wang et al, 2022 ) and counseling ( Ghasemi et al, 2022 ) from universities and institutions of higher education are suggested to alleviate the negative impacts of role conflict and workplace relational conflict in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Offering similar programs to faculty members could decrease stress resulting from their role conflict and lead to less emotional exhaustion, ultimately resulting in lower turnover intention. Third, early intervention and support for such faculty assistance programs ( Wang et al, 2022 ) and counseling ( Ghasemi et al, 2022 ) from universities and institutions of higher education are suggested to alleviate the negative impacts of role conflict and workplace relational conflict in this context.…”
Section: Discussionmentioning
confidence: 99%
“…While an abundance of research has revealed the significance of organization-related events (e.g. workplace bullying, abusive supervision, unreasonable workload and sexual harassment) on employee behaviors (Ariza-Montes et al , 2017; Jung and Yoon, 2018, 2019; Sarwar and Muhammad, 2021; Wang et al , 2022), empirical evidence describing how industry-related events, including the COVID-19 pandemic, lead to employees’ psychological and behavioral outcomes has been negligible (Yu et al , 2021). A systematic understanding of coping strategies in relation to work-related stress for airline employees during the tourism crisis would add new insight into job stress to the hospitality and human resources literature.…”
Section: Background Of Studymentioning
confidence: 99%
“…The majority of its manifestations include compulsion, rudeness, outbursts of rage, and public condemnation (Bies, 2000). Previous studies have provided strong evidence that abusive supervision results in detrimental consequences to subordinates' psychological health and their work-related behaviors in organizations (Bani-Melhem et al, 2021;Farooq & Sultana, 2021;Wang et al, 2022). The organization's ability to survive and achieve long-term success depends critically on this crucial employee's unfavorable reactions to abusive management.…”
Section: Theoretical Underpinnings: Cognitive Appraisal Theory and So...mentioning
confidence: 99%